INTERNALISASI NILAI PENDIDIKAN SOSIAL MELALUI PEMBELAJARAN ADAB SOPAN SANTUN DI KALANGAN SANTRIWATI KELAS I INTENSIF TMI PUTRI AL-AMIEN PRENDUAN TAHUN 2024 - Afifah; Anis Ulfatul Kamilah (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Instillation social education values through learning good manners is one of the most effective ways to teach “Manner and Politeness” to students amidst the increasing number of cases of immorality and disrespect in society. This study aims 1) to analyze the process of internalizing social education values through learning “Manner and Politeness” among female students in grade I intensive TMI Putri Al-Amien Prenduan, 2) to determine the supporting and inhibiting factors in the process of internalizing social education values through learning “Manner and Politeness” among female students in grade I intensive TMI Putri Al-Amien Prenduan. The approach used is qualitative with a case study type. Data collection was carried out through observation, interviews, and documentation. Data were analyzed through the stages of data condensation, data presentation, and drawing conclusions, as well as validation using source triangulation. The results of the study indicate that the internalization of social education values is carried out through three stages, namely: (1) Transformation of values which includes learning planning, (2) Transaction of values in the form of implementation of learning, role models and direct practice, and (3) Trans-internalization of values through role models, supervision, and continuous guidance. Inhibiting factors include the lack of role models from senior female students, the negative influence of peers. Supporting factors are motivation from teachers, kyai and nyai, as well as positive role models from teachers and senior female students.